PENDIDIKAN ISLAM PADA PERIODEISASI KHULAFAUL AL-RASYIDIN - Ahmad Badwi (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2017)
The social patterns of the four caliphs vary. The difference occurs because of different social conditions. At the time of Abu Bakr, some regions wanted to escape from the government with the assumption that his interrelationship with Islam no longer existed when the Messenger of Allah died. At this time the emergence of the apostate, the emergence of false prophets, the rise of the mass of zakat. At the second Caliph the education was more advanced due to the political condition and the society was relatively stable, but in the field of education there was a policy by banning the great companions out of Madinah with the stability of government. So many learners come from outside to study in Medina. Arabic material at this time more interested. Sending some other friends to become governor, as well as a religious leader. At the third Caliph the attitude of Nepotism owned by the Caliph Usman seems to be one cause of the emergence of rebellion in some areas so that the political situation heats up which ends with the killing of Uthman. The pattern of education at this time is not much different from the previous period, but the opportunity for education is wide open so that the senior companions not only settled in Medina but also freely left the city of Madinah to teach. In addition to the codification of the manuscripts headed by Zaid bin Thabit, the great idea is a contribution to Muslims to this day. At the time of the Fourth Caliph this crisis occurred with the emergence of various conflicts of rebellion in some areas and became the cause of stagnation of education during the years of leadership.